Numerical investigation on the effect of draft plates on spouting stability and gas–solid characteristics in a spout-fluid bed. (12th July 2016) - Yang, Shiliang; Sun, Yuhao; Zhang, Liangqi; Zhao, Ya; Chew, Jia Wei
Abstract: Numerical simulation of dense gas–solid motion in a spout-fluid bed was carried out using the computational fluid dynamics coupled with discrete element method (CFD–DEM), in which the gas and solid motion are solved in the Eulerian and Lagrangian framework, respectively. After validating the simulated results with experimental data, the main cause of spouting instability was first identified, followed by evaluating the effect of draft plate length on spouting stability, pressure signals, and gas–solid hydrodynamics in the system. The results demonstrate that the onset of spout dancing, which is a type of spouting instability, is primarily due to the merging of the rising bubbles in the annulus with the spouting channel, which can be circumvented by the presence of draft plates. Increasing the draft plate length diminishes the mean pressure in the spouting inlet and the corresponding peak value of the power spectrum, and the correlation coefficient of pressure signals in the spout and background inlets. Regarding effect on the gas–solid hydrodynamics, a longer draft plate length leads to a more dilute upper spout, a higher spoutable height, higher voidage in the central fountain region, higher vertical gas flux (Fgz) and solid velocity (Usz) in the central axis, lower Fgz and Usz near the wall, and lower vertical solid flux (Fsz) overall. The optimization of the draft plate length depends on a balance between spout stability and solid circulation rate, since the former increases but the latter decreases with draft plate length. Highlights: Spouting stability in a spout-fluid bed was investigated via CFD–DEM. Impact of draft plate with different lengths on improving spouting stability. Draft plates affect gas–solid hydrodynamics in spout, annulus and fountain. Cause of the dancing spout rooted in bubbles merging with spouting channel. Draft plate length optimized by balancing spout stability and solid circulation rate.